How can econometrics help fight the COVID-19 pandemic? - Kevin Alvarez; Vladik Kreinovich (Asian Journal of Economics and Banking (AJEB), 2020)
Purpose - The current pandemic is difficult to model - and thus difficult to control. In contrast to the previous epidemics, whose dynamics were smooth and well described by the existing models, the statistics of the current pandemic are highly oscillating. The purpose of this paper is to explain these oscillations and to see how this explanation can be used to fight the epidemic. Design/methodology/approach - The authors use an analogy with economic systems. Findings - The authors show that these oscillations can be explained if we take into account the disease's long incubation period – as a result of which our control measures are determined by outdated data, showing number of infected people two weeks ago. To better control the pandemic, the authors propose to use the experience of economics, where also the effect of different measures can be observed only after some time. In the past, this led to wild oscillations of the economy, with rapid growth periods followed by devastating crises. In time, economists learned how to smooth the cycles and thus to drastically decrease the corresponding negative effects. The authors hope that this experience can help fight the pandemic. Originality/value - To the best of our knowledge, this is the first explanation of the highly oscillatory nature of this epidemic's dynamics.
Keywords: A12; C50; E17; E32; Y80; 330; Econometrics; COVID-19 pandemic; Oscillatory dynamics; Time-delay systems